Program Bimbingan Belajar Gratis Menggunakan Metode Bernyanyi dan Bermain - Arusman; Aida Safitri; Hanief Furqani; Safrizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract Tutoring is guidance that aims to assist individuals in facing difficulties when studying. There are many teaching methods used by an educator to make children interested and enthusiastic in learning. These methods include singing and playing methods. The purpose of this study was to find out the benefits of free tutoring using the singing and playing method. This study uses a qualitative approach. In collecting data, this study used the observation method. Observations were made to find out the benefits of the singing and playing method when carried out in tutoring. Keywords: Tutoring; Singing Method; Benefit Singing Method